Perubahan Sosial Masyarakat Suku Baduy Luar Sebagai Akibat Moderniasasi - Aprianti, Syapri; Indriyanti, Ade Putri; Lestari, Putri Novianti; Fatihah, Murnia Nur (Ikatan Da'i Indonesia, 2024)
Indonesia is a region that has thousands of islands spread out with different regional characteristics so that it has various tribes and cultures. various social habits, culture and customs of society in Indonesia will always experience developments in accordance with the times. Modernization aims to create a prosperous society. Modernization is one of the causes of social and cultural change. Modernization is the process of changing from a traditional society to a more advanced or modern society. However, not all regions prioritize modernization and forget their customs. This is proven by the fact that there are still regions in Indonesia that still today maintain their customs and culture from the reach of the outside and modern world. For example, the Baduy tribe in the Lebak district, Banten, still maintains and preserves their original culture. The rapid development of the times causing modernization is of course also felt by the Baduy tribe, more precisely by the Baduy community outside. The purpose of this writing is to explain the influence of modernization on the Outer Baduy tribe. The method used in this research is literature study.